Practitioner and landholder perspectives on conservation covenants and extreme weather events - Shirali Davé; Jonathan R. Rhodes; Kelly Fielding; Carla L. Archibald (Conservation Science and Practice)
Abstract Conservation covenants are essential for biodiversity conservation and can offer support to landholders facing climate‐induced challenges. To understand how these events impact landholder livelihoods and their participation in conservation covenant programs, we surveyed conservation practitioners and landholders in New South Wales, Australia. Both covenant adopters and non‐adopting landholders reported similar perceptions of their vulnerability to climate change, though adopters were more optimistic about the potential for covenants to improve their financial wellbeing and environmental outcomes. Practitioners perceived landholders' livelihoods as more threatened by events like drought than landholders themselves reported. Practitioners also perceived changes in program engagement after fire and during drought, though opinions varied on whether these events had a positive or negative influence on participation. Understanding how climate events affect covenant participation provides important insights for strengthening landholder resilience and enhancing future program participation.